Advice Giving: A Subtle Pathway to Power. (May 2018) - Schaerer, Michael; Tost, Leigh P.; Huang, Li; Gino, Francesca; Larrick, Rick
We propose that interpersonal behaviors can activate feelings of power, and we examine this idea in the context of advice giving. Specifically, we show (a) that advice giving is an interpersonal behavior that enhances individuals' sense of power and (b) that those who seek power are motivated to engage in advice giving. Four studies, including two experiments ( N = 290, N = 188), an organization-based field study ( N = 94), and a negotiation simulation ( N = 124), demonstrate that giving advice enhances the adviser's sense of power because it gives the adviser perceived influence over others' actions. Two of our studies further demonstrate that people with a high tendency to seek power are more likely to give advice than those with a low tendency. This research establishes advice giving as a subtle route to a sense of power, shows that the desire to feel powerful motivates advice giving, and highlights the dynamic interplay between power and advice.